Applying Citizens' Juries to the Global South: Facilitation guidelines using the case study of agricultural food system transformation in Colombia - Nilgen, Marco; Untermayer, Lena; Vollan, Björn (CGIAR, 2023)
Citizen's juries (CJs) are a form of deliberative democracy that can help promote public participation in decision-making processes. CJs are typically described as a randomly selected group of people, which are gathered to represent a microcosm of their respective communities. Typically, over the course of one to six full days (depending on the scope and complexity of the issue at hand), the jurors meet to learn and discuss public policy issues. Led by a neutral moderator, these proceedings are informed by invited experts on the policy issue at hand. These experts should ideally reflect several points of view on the topic at hand in a fair and unbiased manner. After careful deliberation, CJs are ultimately expected to make conclusive policy recommendations (Crosby, 1995; Lenaghan, 1999; Street et al., 2014). CJs have been used in many countries around the world in a variety of different policy contexts and have proven to be an effective way to engage citizens in decision-making when implemented well (Aldred & Jacobs, 2000; Coote & Lenaghan, 1997; Fishkin et al., 2017; Kenyon et al., 2010; Kuper, 2007; Wakeford et al., 2015). However, conducting CJs in the Global South poses unique challenges that require careful consideration (Fishkin et al., 2017; Humphreys et al., 2006; Pimbert et al., 2001, 2010, 2017). This document provides facilitation guidelines informed by a detailed literature review on CJ instructions in general (e.g., The Jefferson Center, 2004), as well as specific recommendations to safeguard an optimized implementation of the methodology in the Global South.